Juridical review of Consumer Dispute Resolution in Online Marketplace Transactions - Hanuring Ayu; Lahmuddin Zuhri; Olyvia Rosalia; Firayani (PT. Anagata Sembagi Education, 2025)
The development of digital technology has driven the growth of online transactions through marketplace platforms, providing convenience for consumers in shopping. However, as electronic transactions increase, various disputes have arisen between consumers and business actors, such as mismatched products, delayed deliveries, and fraud. This study aims to examine the consumer dispute resolution mechanisms in marketplace transactions from a legal perspective, assess the effectiveness of existing regulations, and identify the challenges faced in their implementation. The research method used is normative legal research with a statutory approach and a conceptual approach. The results of the study show that existing regulations, such as the Consumer Protection Law and the Electronic Information and Transactions Law (ITE Law), have not been fully effective in providing legal certainty for consumers. Differences in dispute resolution mechanisms across marketplaces and low consumer legal literacy are the main obstacles in protecting consumer rights. Therefore, it is necessary to strengthen regulations, ensure transparency in dispute resolution procedures, and improve consumer education to optimize the consumer protection system in electronic transactions.